LEARNING STYLES: HUMPTY DUMPTY REVISITED - Ivie, Stan D. (Revue des sciences de l’éducation de McGill / McGill Journal of Education, 2009)
ABSTRACT. What is a learning style? No one seems to know for sure. The language used by learning style theorists is filled with ambiguities. Price (2004) maintains that “learning style is often used as a metaphor for considering the range of individual differences in learning᾿ (p. 681). Is learning style merely a fanciful metaphor or is it the wave of the future? The research offers mixed results. “Effects on improved test scores with testing conditions matched to student style have been published, but,᾿ Curry (1990) adds, “there are also studies showing no discernible effect attributable to learning style variation᾿ (p. 54). How many distinct learning style models are there? The Coffield (2004) team identified 71 different learning style models, which they subdivided into 13 major and 58 minor models. One of the most popular learning style models comes from Rita and Kenneth Dunn. They have developed an eclectic model featuring 21 (23) different variables that influence a person’s learning style. These variables run all the way from light and temperature to whether the person is analytic or global in his or her thinking. Rita Dunn says about the movement: “I want to convert the world᾿ (Kortland, 2007, p. 8). And well she may. The Dunns’ model is used in the United States, Canada, Great Britain, Australia, and a number of other countries. Is learning style a panacea or a placebo? The jury is still out on that question. STYLES D’APPRENTISSAGE : HUMPTY DUMPTY REVISITÉ RéSUMÉ. Qu’est-ce qu’un style d’apprentissage? Nul ne semble tout à fait certain de ce que cela signifie. Le vocabulaire utilisé par les théoriciens des styles d’apprentissages est truffé d’ambiguïtés. Price (2004) soutient que le terme « style d’apprentissage est fréquemment utilisé comme une métaphore pour refléter l’éventail des différences individuelles face à l’apprentissage.» (p. 681) En fait, les chercheurs présentent des résultats variés. Selon Curry (1990), « si des effets positifs sur les résultats de tests dont les conditions respectaient le style d’apprentissage de l’étudiant ont été publiés, il existe également des études démontrant qu’il n’existe pas d’effet significatif attribuable à la variation des styles d’apprentissage. » (p. 54) Combien de styles d’apprentissage distincts peut-on répertorier? L’équipe de Coffield (2004) a identifié 71 théories différentes sur les styles d’apprentissages, en admettant toutefois qu’il pourrait en exister jusqu’à 100. Un des styles d’apprentissages les plus connus est celui popularisé par Rita et Kenneth Dunn. Ceux-ci ont développé un modèle éclectique montrant 21 (23) variables différentes qui influencent le style d’apprentissage d’un individu. Ces variables comportent autant la manière dont la lumière, la température ou encore la personnalité analytique ou globale d’un individu influence son mode de pensée. À propos de ce mouvement, Rita Dunn déclare : « Je désire convertir le monde » (Kortland, 2007, p. 8). Elle le fera peut-être. Le modèle Dunn est utilisé aux États-Unis, au Canada, en Grande-Bretagne, en Australie et dans un grand nombre d’autres pays. Le style d’apprentissage est-il une panacée ou un effet placébo? Le jury délibère encore sur la question.